The Use of Children's Traditional Games as an Effort to Preserve Indonesia's Cultural Heritage and Increase Students Speaking Skills - Dewi, Ratna Sari (PROJECT (Professional Journal of English Education), 2025)
This study aims to understand the efforts and strategic steps that can be taken to preserve traditional games in keeping with Indonesia's cultural legacy and to identify the factors that necessitate the use of children's traditional games in student speaking skills. This research method uses a qualitative approach with a phenomenological approach. In-depth interviews, documentation, and observation are the methods of data collection employed in this study. To obtain a natural knowledge of the research data, the data collection, reduction, interpretation, and conclusion-drawing processes are conducted dialogically using the data analysis technique known as interactive data analysis. The findings of this investigation show that there are 4 strategic steps that partners can take to preserve traditional games as a cultural heritage, including education and socialization, revitalization and modernization, community empowerment and engagement, as well as collaboration with the private sector. There are 7 factors that require the use of traditional children's games at MIS Syababul Qorib, including the decline in interest in traditional games, preservation of local culture, the influence of globalization, the developmental benefits of traditional games for children, the lack of opportunities to play at school, support for character education, stimulate student speaking skill and the increased social interaction in the digital era.